2022
DOI: 10.1002/mp.16056
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐specific transfer learning for auto‐segmentation in adaptive 0.35 T MRgRT of prostate cancer: a bi‐centric evaluation

Abstract: Background: Online adaptive radiation therapy (RT) using hybrid magnetic resonance linear accelerators (MR-Linacs) can administer a tailored radiation dose at each treatment fraction. Daily MR imaging followed by organ and target segmentation adjustments allow to capture anatomical changes, improve target volume coverage, and reduce the risk of side effects. The introduction of automatic segmentation techniques could help to further improve the online adaptive workflow by shortening the re-contouring time and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Kawula et al utilized transfer learning to develop patient-specific (PS) and facility-specific (FS) models on magnetic resonance imaging. 36 The PS model reported a significant improvement, whereas the FS model did not improve the performance significantly. Feng et al implemented a transfer learning strategy to overcome the data heterogeneity problem in thoracic cases and successfully improved the sub-optimal performance for cases with abdominal compression.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Kawula et al utilized transfer learning to develop patient-specific (PS) and facility-specific (FS) models on magnetic resonance imaging. 36 The PS model reported a significant improvement, whereas the FS model did not improve the performance significantly. Feng et al implemented a transfer learning strategy to overcome the data heterogeneity problem in thoracic cases and successfully improved the sub-optimal performance for cases with abdominal compression.…”
Section: Discussionmentioning
confidence: 89%
“…Kawula et al. utilized transfer learning to develop patient‐specific (PS) and facility‐specific (FS) models on magnetic resonance imaging 36 . The PS model reported a significant improvement, whereas the FS model did not improve the performance significantly.…”
Section: Discussionmentioning
confidence: 99%
“…30 Recent work by Kawula et al utilized the fine-tuning approach to create patient-specific DL models in ART auto-segmentation. 31 In a study by Chun et al, they demonstrated that the intentional deep overfit learning (IDOL) approach to training a patient-specific DL model yielded statistically significant improvement over a generalized DL model in three ART tasks-auto-segmentation, super-resolution for magnetic resonance imaging (MRI), and synthetic CT reconstruction based on MRI. 32 Our previous work explored the application of the IDOL approach toward fine-tuning dose predictions in ART.…”
Section: Introductionmentioning
confidence: 99%
“…The DL model trained from popular data will not perform well when applied to new and unseen cases. [26][27][28][29] The existing DIR and DL methods are suboptimal, so the development of a reliable and efficient automatic segmentation algorithm is an urgent need of online MRI-guided prostate radiotherapy. Ding et al 27,28 developed a DL-based automatic contour refinement to correct the segmentation errors in regular method.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, significant intensity inhomogeneities among MR images across patients can be observed even with the same scanner. The DL model trained from popular data will not perform well when applied to new and unseen cases 26–29 …”
Section: Introductionmentioning
confidence: 99%